PENGARUH PEMBELAN KOOPERATIF TIPE JIGSAW TERHADAP PENGUASAAN KONSEP BELAJAR SISWA PADA MATA PELAJARAN BIOLOGI KELAS X MA NW SENYIUR TAHUN PELAJARAN - Aini, Isnawatul; Asri, Indra Himayatul; Ariandani, Nunung; Wazni, M Khairul; Fathoni, Ahmad (UNIVERSITAS HAMZANWADI, 2022)
Target of this research is to know do there [is] influence of study of type cooperative of jigsaw to domination of concept learn student [at] biological subject [of] classof X MA NW Senyiur School Year 2021. this Research type [of] experiment quasi by usingtype co-operative model of jigsaw in the form of design group control post-test-only.Subjek in this [is] all class student of XII IPA MA NW Senyiur School Year 2021.Population in all these research [of] class of X IPA which consist of one class with amount23 student people and class of X IPS which consist of one class with amount 24 studentpeople of MA NW Senyiur. Sampel in this research [is] class of X-Ipa as experiment classand class of X-Ips as control class. Intrumen in this research in the form of tes dominationof concept learn in the form of double helix amounting to 20 problem item which have [in]validasi. Pursuant to result of data analysis obtained [by] value flatten - flatten experimentclass post-test namely 63 and class control namely 54.708. While, hypothesis test usestatistical analysis with formula of uji-t [at] trust level 5% obtained [by] t-hitung equal to2.419. After compared to t-tabel ( 1.680), hence t-hitung ( 2.419) > t-tabel ( 1.680). so thatcan be concluded that there is influence of study of type co-operative of jigsaw todomination of conceptlearn student [at] biological subject [of] class of X MA NW SenyiurSchool Year 2021.